malERA: An updated research agenda for malaria elimination and eradication. - Regina N Rabinovich; Chris Drakeley; Abdoulaye A Djimde; B Fenton Hall; Simon I Hay; Janet Hemingway; David C Kaslow; Abdisalan Noor; Fredros Okumu; Richard Steketee; Marcel Tanner; Timothy N C Wells; et al. (PLoS Medicine)
Achieving a malaria-free world presents exciting scientific challenges as well as overwhelming health, equity, and economic benefits. WHO and countries are setting ambitious goals for reducing the burden and eliminating malaria through the "Global Technical Strategy" and 21 countries are aiming to eliminate malaria by 2020. The commitment to achieve these targets should be celebrated. However, the need for innovation to achieve these goals, sustain elimination, and free the world of malaria is greater than ever. Over 180 experts across multiple disciplines are engaged in the Malaria Eradication Research Agenda (malERA) Refresh process to address problems that need to be solved. The result is a research and development agenda to accelerate malaria elimination and, in the longer term, transform the malaria community's ability to eradicate it globally.